(3GdJObjb GdeMGSHj OQhS hJWHjbGJs - (3aGWeI GdRgQGA(B, (3QbGjbjIs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2020)
(3JfGhd gPG GdcJGH ehVhY GdJObjb GdeMGSHj MjK JMOK ef NdGd aUhd OQGSJg GdEWGQ GdeaGgjej hGdJGQjNj ddQbGHI hGdJObjb, hfXGe GdQbGHI GdOGNdjI hGdJObjb GdOGNdj, hGdCNWGA hJUMjMgG, HGdGVGaI Gdi GdJObjb aj OhQI GdESJKeGQGJ haj OhQI GdeNRhf haj OhQI GdeTJQjGJ hGdeHjYGJ haj OhQI GdCLhQ haj GdOhQI GdfbOjI , haj GdCNjQ JMOK Yf JbQjQ eMGaX GdMSGHGJ(B. s
(3GdeQGLY U(B.119s
Keywords: (3GdQbGHI GdeGdjIs